Designing specific test to profile sepak takraw players - Singh, Rabindarjeet
A wireless miniature accelerometer namely 'Sports Accel' was designed to record the acceleration of the service kick in Sepaktakraw. This accelerometer, which was attached to the kicking service leg, could detect acceleration up to ±250 g (each g 9.81 m/s) was connected to a transmitter which has a 24 bit AID with a sampling rate of 70 samples/sec. Through a microcontroller the transmitter can transfer data to a computer via an antenna at a rate of 9 Kbit/sec with a radio transmitter distance of up to 200 meters. A special so!tWare was tehn designed to save and show the all parameters obtained during the service kick . Methods: Eight (8) Sepaktakraw tekongs (age between 18-21 years and leg length 1 01.4±5.4 em) participated in this preliminary trial. The sensor was placed on to the service leg. Peak tibia acceleration, service kick duration, maximum acceleration and maximum velocity were obtained during the service kick. The data obtained were then averaged over 1 0 trials by each tekong. The peak tibia acceleration, service kick duration, maximum acceleration and maximum velocity obtained were 7.0 ± 2.8 g, 187.3 ± 9.9 msec, 41.6 ± 22.4 g/s2 , 407.6 ± 21.9 m/s2 respectively. Results: There was a significant and positive correlation (r=0.26, p<0.02) between leg length and maximum velocity but negative correlation between leg length and duration of a service kick. Peak tibia acceleration significantly correlated with maximum acceleration (r=0.57, p<0.001), are there was a strong correlation between maximum acceleration and velocity. However, there was a negative correlation between maximum acceleration and kicking duration of a service. Conclusion: These data are the first ever measurements of velocity and acceleration obtained from the service kick of Sepaktakraw tekongs.